The schooling of irregular migrant children in Canada - Passarelli, D (2017)
This thesis examines the practice of accommodating irregular migrant children in Canadian public schools, specifically, public schools in Toronto, Ontario. Estimates indicate that there are close to 500,000 irregular migrants in Canada; half are thought to be living in the City of Toronto. Since the early 1990s there have been several novel policy developments in Ontario that have facilitated access to public schooling for irregular migrant children. This project seeks to identify the normative ideas that have been appealed to by public authorities in the policy development process. First, a critical review is undertaken of theoretical justifications developed in moral and political theory for extending schooling rights to irregular migrant children in liberal states. Then, arguments put forward by public authorities in Canada for extending or limiting schooling rights are analysed and compared with the dominant normative frameworks in the theoretical literature. This research finds that public authorities at the sub-state level made use of normative arguments that fall outside common theoretical approaches in moral and political theory. Normative arguments at the sub-state level are found to cohere with a fiduciary conception of public authority. It is argued that fiduciary theory provides a systematic and innovative theoretical framework for understanding the normative ideas appealed to by public authorities in practice. Moreover, fiduciary theory makes available the normative resources necessary to provide a strong way of conceptualising the duty of public authorities to educate irregular migrant children. This research contributes both to theoretical scholarship aimed at understanding and conceptualizing obligations to irregular migrant children, and also to the field of Canadian Studies, by contextualizing the policy response to irregular migrant children in Canada over time, demonstrating how specific policy responses reflect shifting normative understandings about belonging, government obligation, national culture(s) of citizenship, and the scope of provision of social welfare services to irregular migrant children.